The Hague Convention Framework Development of Criminal Weapon as Domestic Violence Market Problem of Aggressive Tax as Intimate Partner Deontology - Zharama Llarena (Journal of Diplomacy and International Studies, 2022)
Corporate Governance is a systematic design of stakeholders and their corporate social responsibility to advocate sustainable development. Tax aggressiveness is the obligation of the company to provide revenue distribution to public sector. Unlawful behavior on tax aggressiveness is known as tax evasion while tax avoidance is not a violation and serves as a loophole to the taxation system. UNCITRAL model law is a legal arbitration concept of making “commercial” expand to other comparable jurisdiction of international trade. Hague Convention drafted travaux preparatoires to conceptualize a legal framework of making the commercial transactions universal to other extended territories in terms of international trade law. This paper aims to develop tax avoidance based on statutory interpretation concerning Hague Convention as its extrinsic material to extend the legal principle of travaux preparatoires, hence, utilizing UNCITRAL legal modelling framework to make commercial transactions universal to trade law, for addressing legal gaps in marketing behavior of taxation system involving intellectual property, thus, in lack of legal measures in protecting public safety resulting to increase in domestic violence proportional to massive terrorism serving as professional deontology problem. Therefore, in terms of tax avoidance, the strict liability of the company must be addressed with constitutional issues and commercial responsibilities of marketing its product designed with elemental performance of domestic violence.